2011
DOI: 10.1051/0004-6361/201016342
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory motions observed in eruptive filaments

Abstract: Context. The origin of the variable component of the solar wind is of great intrinsic interest for heliophysics and spaceweather, e.g. the initiation of coronal mass ejections and the problem of mass loss of all stars. It is also related to the physics of coronal neutral sheets and streamers, which occur above lines of magnetic polarity reversal. Filaments and prominences correspond to the cool coronal component of these regions. Aims. We examine the dynamical behaviour of these structures where reconnection a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…Therefore, based on this line of thought and spectroscopic observations of an oscillating prominence prior to eruption, Chen et al (2008) proposed that long-time prominence oscillations can be considered as one of the precursors of CME eruptions. A prominence oscillation prior to eruption was also observed by Bocchialini et al (2011), and the oscillation was even able to be sustained until the eruption phase (Isobe & Tripathi 2006;Gosain et al 2009). The restoring force in this kind of transverse oscillations was generally thought to be the magnetic tension force.…”
Section: Introductionmentioning
confidence: 90%
“…Therefore, based on this line of thought and spectroscopic observations of an oscillating prominence prior to eruption, Chen et al (2008) proposed that long-time prominence oscillations can be considered as one of the precursors of CME eruptions. A prominence oscillation prior to eruption was also observed by Bocchialini et al (2011), and the oscillation was even able to be sustained until the eruption phase (Isobe & Tripathi 2006;Gosain et al 2009). The restoring force in this kind of transverse oscillations was generally thought to be the magnetic tension force.…”
Section: Introductionmentioning
confidence: 90%
“…(9) and (13) allow for seismological diagnostics of the current in the prominence. For example, taking a typical value of P KR ≈ 20 min (Kuperus & Raadu 1974) and fixing h = 0.6 d, for the observed periods of the vertical transverse oscillations, P z ≈ 80 min (Bocchialini et al 2011), the prominence current i with respect to the photospheric current I, according to Eq. (9), can be estimated as I ≈ 0.94 i.…”
Section: Discussionmentioning
confidence: 99%
“…Both vertically (e.g. Bocchialini et al 2011;Kim et al 2014) and horizontally polarised (e.g. Kleczek & Kuperus 1969;MolownyHoras et al 1997;Tripathi et al 2009) motions of prominences have been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Outside of active regions coronal oscillations were reported off-disk in the range of 5 min periods (Tsubaki, 1977;Tomczyk et al 2007) and also at shorter periods (Koutchmy et al 1983). Evidences of such dynamical processes were also reported for eruptive filaments (e.g., Bocchialini et al 2011), and magnetoacoustic waves were recorded on-disk inside an anomalously bright network rosettes using simultaneous observations in 3 photospheric and chromospheric lines (Baudin et al, 1996). When considering a higher spatial resolution, even finer scales and faster variations are observed (Cirtain et al 2013).…”
Section: Introductionmentioning
confidence: 98%